Pharmacodynamics of Aerosolized Fosfomycin and Amikacin against Resistant Clinical Isolates of Pseudomonas aeruginosa and Klebsiella pneumoniae in a Hollow-Fiber Infection Model: Experimental Basis for Combination Therapy - Sime, Fekade Bruck (Antimicrob Agents Chemother, 2016)
There has been a resurgence of interest in aerosolization of antibiotics for treatment of patients with severe pneumonia caused by multidrug-resistant pathogens. A combination formulation of amikacin-fosfomycin is currently undergoing clinical testing although the exposure-response relationships of these drugs have not been fully characterized. The aim of this study was to describe the individual and combined antibacterial effects of simulated epithelial lining fluid exposures of aerosolized amikacin and fosfomycin against resistant clinical isolates of Pseudomonas aeruginosa (MICs of 16 mg/liter and 64 mg/liter) and Klebsiella pneumoniae (MICs of 2 mg/liter and 64 mg/liter) using a dynamic hollow-fiber infection model over 7 days. Targeted peak concentrations of 300 mg/liter amikacin and/or 1,200 mg/liter fosfomycin as a 12-hourly dosing regimens were used. Quantitative cultures were performed to describe changes in concentrations of the total and resistant bacterial populations. The targeted starting inoculum was 10(8) CFU/ml for both strains. We observed that neither amikacin nor fosfomycin monotherapy was bactericidal against P. aeruginosa while both were associated with rapid amplification of resistant P. aeruginosa strains (about 10(8) to 10(9) CFU/ml within 24 to 48 h). For K. pneumoniae, amikacin but not fosfomycin was bactericidal. When both drugs were combined, a rapid killing was observed for P. aeruginosa and K. pneumoniae (6-log kill within 24 h). Furthermore, the combination of amikacin and fosfomycin effectively suppressed growth of resistant strains of P. aeruginosa and K. pneumoniae. In conclusion, the combination of amikacin and fosfomycin was effective at maximizing bacterial killing and suppressing emergence of resistance against these clinical isolates.